EULAR evidence based recommendations for the management of hip osteoarthritis: report of a task force of the EULAR Standing Committee for International Clinical Studies Including Therapeutics (ESCISIT). Issue 5 (7th October 2004) - Zhang, W; Doherty, M; Arden, N; Bannwarth, B; Bijlsma, J; Gunther, K-P; Hauselmann, H J; Herrero-Beaumont, G; Jordan, K; Kaklamanis, P; Leeb, B; Lequesne, M; et al.
Abstract : Objective: To develop evidence based recommendations for the management of hip osteoarthritis (OA). Methods: The multidisciplinary guideline development group comprised 18 rheumatologists, 4 orthopaedic surgeons, and 1 epidemiologist, representing 14 European countries. Each participant contributed up to 10 propositions describing key clinical aspects of hip OA management. Ten final recommendations were agreed using a Delphi consensus approach. Medline, Embase, CINAHL, Cochrane Library, and HTA reports were searched systematically to obtain research evidence for each proposition. Where possible, outcome data for efficacy, adverse effects, and cost effectiveness were abstracted. Effect size, rate ratio, number needed to treat, and incremental cost effectiveness ratio were calculated. The quality of evidence was categorised according to the evidence hierarchy. The strength of recommendation was assessed using the traditional A–D grading scale and a visual analogue scale. Results: Ten key treatment propositions were generated through three Delphi rounds. They included 21 interventions, such as paracetamol, NSAIDs, symptomatic slow acting disease modifying drugs, opioids, intra-articular steroids, non-pharmacological treatment, total hip replacement, osteotomy, and two general propositions. 461 studies were identified from the literature search for the proposed interventions of efficacy, side effects, and cost effectiveness. Research evidence supported 15 interventions in the treatment of hip OA. Evidence specific for the hip was strikingly lacking. Strength of recommendation varied according to category of research evidence and expert opinion. Conclusion: Ten key recommendations for the treatment of hip OA were developed based on research evidence and expert consensus. The effectiveness and cost effectiveness of these recommendations were evaluated and the strength of recommendation was scored.